Fenebrutinib Versus Placebo or Adalimumab in Rheumatoid Arthritis: A Randomized, Double‐Blind, Phase II Trial. Issue 9 (28th August 2020) - Cohen, Stanley; Tuckwell, Katie; Katsumoto, Tamiko R.; Zhao, Rui; Galanter, Joshua; Lee, Chin; Rae, Julie; Toth, Balazs; Ramamoorthi, Nandhini; Hackney, Jason A.; Berman, Alberto; Damjanov, Nemanja; et al.
Abstract : Objective: To evaluate fenebrutinib, an oral and highly selective noncovalent inhibitor of Bruton's tyrosine kinase (BTK), in patients with active rheumatoid arthritis (RA). Methods: Patients with RA and an inadequate response to methotrexate (MTX) (cohort 1; n = 480) were randomized to receive fenebrutinib (50 mg once daily, 150 mg once daily, or 200 mg twice daily), adalimumab (40 mg every other week), or placebo. Patients with RA and an inadequate response to tumor necrosis factor inhibitors (cohort 2; n = 98) received fenebrutinib (200 mg twice daily) or placebo. Both cohorts continued MTX therapy. Results: In cohort 1, the percentages of patients in whom American College of Rheumatology 50% improvement criteria (ACR50) was achieved at week 12 were similar in the fenebrutinib 50 mg once daily and placebo groups, and were higher in the fenebrutinib 150 mg once daily group (28%) and 200 mg twice daily group (35%) than in the placebo group (15%) ( P = 0.016 and P = 0.0003, respectively). Fenebrutinib 200 mg twice daily and adalimumab (36%) were comparable ( P = 0.81). In cohort 2, ACR50 was achieved in more patients receiving fenebrutinib 200 mg twice daily (25%) than placebo (12%) ( P = 0.072). The most common adverse events in the fenebrutinib groups included nausea, headache, anemia, and upper respiratory tract infections. Fenebrutinib had significant effects on myeloid and B cell biomarkers (CCL4 and rheumatoid factor). Fenebrutinib and adalimumab caused overlapping as well as distinct changes in B cell and myeloid biomarkers. Conclusion: Fenebrutinib demonstrates efficacy comparable to adalimumab in patients with an inadequate response to MTX, and safety consistent with existing immunomodulatory therapies for RA. These data support targeting both B and myeloid cells via this novel mechanism for potential efficacy in the treatment of RA.